Nutrient profiling assessment of packaged snack foods with nutrition-related claims available on the Indian market - Bhatnagar, Amisha; Choudhary, Monika; Kumar, Vikas; Singh, Vicky; Kaur, Prabhdeep (Frontiers in Nutrition, 2024)
Background Food packaging includes labels with specific nutrient contents to provide consumers with nutritional information. Legislative actions and consumers’ growing interest in nutrition information have increased the disclosure of nutrition information. The study was planned to examine packaged snack foods carrying nutritional claims for nutrition labeling. Methods The selected packaged chips were divided into categories based on the primary ingredients mentioned on the nutrition label, such as cereal/pseudocereal-based, millet-based, vegetable-based, and pulses/legume-based chips. Four threshold levels, such as total sugar, sodium, total fat, and saturated fat, were used for categorization. Results Out of a total of 23 packaged chips, the corresponding 2, 7, 8, and 13 products had a higher content of sugar, saturated fat, sodium, and total fat than the threshold levels. A significant (p ≤ 0.01) difference was observed in the values of nutrients analyzed through laboratory methods in comparison with the values given on the nutrition label in the majority of the products. Conclusion The majority of the products belonged to national brands and differed from the nutrition-related information given on the product label in terms of the nutrient content claim.